The interface between biochemical signaling and cell mechanics shapes T lymphocyte migration and activation - María Millán-Salanova (European Journal of Cell Biology, 2022)
tT cells migrate to lymphoid organs to become activated through specific contacts with antigen-presenting cells bearing foreign antigens. During migration and activation, T lymphocytes are exposed not only to diverse biochemical inputs, but also to different mechanical conditions. Passage from the blood or lymph to solid tissues involves lymphocyte rolling, firm arrest and diapedesis through endothelial monolayers. Throughout this process, cells are subjected to diverse fluid flow regimes. After extravasation, T lymphocytes crawl through viscoelastic media of different biochemical and mechanical properties and geometries. In lymph nodes, T cell contact with antigen-presenting cells is guided by rigidity cues and ligand-receptor interactions. T lymphocyte adaptation to diverse mechanical regimes involves multiple signaling and morphological modifications, many of which enable the conversion of mechanical forces into biochemical signals and vice-versa. These components enable T lymphocyte survival, homing and activation. Here, we review the mechanisms that enable T lymphocytes to survive and thrive under the different mechanical conditions they encounter during their life cycle. These processes require the integration of diverse signaling networks that convert extracellular mechano-chemical cues into force, movement and activation.